Length-Weight, Condition Factor And Feeding Guild Periophthalmus Chrysospilos (Bleeker, 1852) (Gobiidae: Oxudercinae), From Bayan Bay Coastal Water, Penang - Abdullah, Mohd Ilman Che (2016)
A study on population dynamics and feeding biology of mudskipper, periophthalmus chrysospilos was conducted in bayan bay coastal water, penang from july 2013 to july 2014. This study comprised of three components: (i) length-weight relationships (lwr) and fulton condition factor (k); (ii) growth, mortality, and recruitment pattern, and (iii) stomach content analyses. The main objectives of this study are: (i) to investigate the length-weight relationships of p. Chrysospilos in different sexes and months, (ii) to elucidate the fulton condition factor and its relation to the monthly variations and water physio-chemical parameters, (iii) to study the growth parameters, mortality and recruitment pattern of p. Chrysospilos and finally (iv) to determine the feeding activities and feeding guild of p. Chrysospilos according to different sex, months and water tide. Results show the exponential values (zj) of the lwr for all individuals (n = 714), male and female fish, and fish caught during dry and rainy months were greater than 3, indicating of positive allometric growth. The fulton’s condition factor (k) for all individuals, male, female, and fish caught in dry and rainy months were 0.998 ± 0.121, 0.9907 ± 0.106, 1.008 ±0.138, 1.018 ± 0.115 and 0.998 ± 0.123, respectively. The b and k values for male and female fish were not significantly different. The b value in dry months is significantly higher than in rainy months.